QM/MM reveals the sequence of substrate binding during OPRT action. (June 2018) - Subrahmanyeswara Rao, N.N.; Deshpande, Parag A.
Graphical abstract: Highlights: QM/MM framework applied to describe PRPP and OA binding with OPRT. Four pathways explored for metal-PRPP-OA-OPRT complex formation. Energetics developed for all reaction pathways. Divalent metal ions found to be essential for PRPP complexation. A series of experimental observations of substrate binding explained. Abstract: Computational investigation of orotate phosphoribosyltransferase (OPRT) action, an enzymatic reaction between phosphoribosyl pyrophosphate (PRPP) and orotic acid (OA) to yield orotidine 5′-monophosphate (OMP), was carried out. Insights into the pathways of the substrate attack step of the reaction were developed under the quantum mechanics/molecular mechanics framework with S. cerevisiae strain as the representative enzyme bearer. Four pathways were proposed for PRPP and OA binding differing in the sequence of PRPP, OA and Mg 2+ ion complexation with OPRT. The formation of Mg 2+ -OPRT complex was accompanied by a small energy change while the largest stabilization was observed for the formation of Mg 2+ -PRPP complex supporting the experimental observation of Mg 2+ -PRPP complex as the true substrate for the reaction. Formation of PRPP-OPRT complex was found to be energetically not probable rendering the pathway requiring Mg 2+ -OA complex not probable. Further, PRPP migration towards the active site was found to be energetically not favoured rendering the pathway involving Mg 2+ -OA complexation improbable. Migration of OA and Mg 2+ -PRPP complex towards the active site was found to be energetically probable with a large stabilization of the system when Mg 2+ -PRPP complex bound to the OA-OPRT complex. This conclusively proved the sequential binding of OA and Mg 2+ -PRPP complexes during OPRT action.